Pengaruh Getaran Centrifuge Terhadap Hasil Pemeriksaan Laju Endap Darah (LED) - Muhammad Nazarudin (Jurnal Labora Medika, 2019)
The Erythrocyte Sedimentation Rate (LED) is a hematological examination which is a preliminary examination in establishing a patient's diagnosis. Many LED tests have factors that can affect the results, one of them is vibration. In some health service units, LED checks are carried out close to the Centrifuge, which has vibrations, for reasons of room efficiency. This study aims to determine the effect of Centrifuge vibration on the results of the Westergren method LED examination. The study was conducted with 6 repetitions. This type of research used is quasi-experimental with static group comparison design. The research obtained is presented in table form, followed by ANOVA test. ANOVA test gives a significant value of 0.305 which indicates that there is no significant effect by the vibration of the Centrifuge on the LED results with variations in the distance of 0.5m, 1m, and 1.5m